PERENCANAAN PENJADWALAN TENAGA KERJA PADA UKM SONGKOK IKAT KEPALA - Welly Bachtria Nugroho (Manajemen Bisnis, 2018)
Songkok Ikat Kepala was one of UKM which produce songkok in Gresik. This UKM Songkok Ikat Kepala was produced by strategy “make to order” and there was no guideline for period production. Problems that occurred were known asdelayed production process at the process of sewing. The aim of this study was (1) to analyze the planning of labor scheduling and (2) to determine the standard of estimation of item production process. The data were analyzed by using period study and gantt diagram techniques. The results of the study showed that there were 2 standards of estimation, those are fast and low standards. Fast standard needed the work estimation in 444 seconds. However, low standard needed the work estimation in 536 seconds. Therefore, this study was expected to be guidance to arrange the schedule by using gantt diagram.